Pancasila Sebagai Pedoman Kehidupan Bagi Generasi Muda - Muhammad Bayu Al Ghifari (Universitas Pembangunan Nasional Veteran Yogyakarta, 2021)
This study aims to describe the views of the younger generation of Indonesia on the existence of Pancasila as the ideology of the Indonesian nation. The existence of Pancasila is something that is very valuable for this nation, especially for the younger generation of Indonesia who will then continue the baton of struggle to realize an advanced and prosperous Indonesia and realize the ideals of its predecessors. But nowadays, the younger generation of Indonesia no longer adheres to the values of Pancasila as the state ideology and then applies them in their daily lives. The method used in this study uses a qualitative approach. The data used in this study were obtained from scientific journals, news, and previous research results. Analysis of the data used in this study using analytical descriptive analysis. The results of this study indicate that the younger generation actually has knowledge about the practice of Pancasila but lacks in its implementation. The younger generation is still unable to implement and live the values of Pancasila because they are distracted by various kinds of national problems which are certainly not in line with the noble values of Pancasila.